A critical review of front‐loading: A maladaptive drinking pattern driven by alcohol's rewarding effects. (14th October 2022) - Ardinger, Cherish E.; Lapish, Christopher C.; Czachowski, Cristine L.; Grahame, Nicholas J.
Abstract: Front‐loading is a drinking pattern in which alcohol intake is skewed toward the onset of reward access. This phenomenon has been reported across several different alcohol self‐administration protocols in a wide variety of species, including humans. The hypothesis of the current review is that front‐loading emerges in response to the rewarding effects of alcohol and can be used to measure the motivation to consume alcohol. Alternative or additional hypotheses that we consider and contrast with the main hypothesis are that: (1) front‐loading is directed at overcoming behavioral and/or metabolic tolerance and (2) front‐loading is driven by negative reinforcement. Evidence for each of these explanations is reviewed. We also consider how front‐loading has been evaluated statistically in previous research and make recommendations for defining this intake pattern in future studies. Because front‐loading may predict long‐term maladaptive alcohol drinking patterns leading to the development of alcohol use disorder (AUD), several future directions are proposed to elucidate the relationship between front‐loading and AUD. Abstract : Front‐loading is a drinking pattern where intake is skewed toward the onset of reward access. This phenomenon has been reported across different alcohol self‐administration protocols using a variety of species, including humans. The hypothesis of the current review is that front‐loading emerges in response to the rewarding effects of alcohol and can be used as a measure of motivation to consume alcohol. Alternative hypotheses are assessed, and several future directions are proposed to elucidate the relationship between front‐loading and AUD.